2021
DOI: 10.1038/s41419-021-03804-7
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule inhibition of APE1 induces apoptosis, pyroptosis, and necroptosis in non-small cell lung cancer

Abstract: Apurinic/apyrimidinic endonuclease 1 (APE1) plays a critical role in the base excision repair (BER) pathway, which is responsible for the excision of apurinic sites (AP sites). In non-small cell lung cancer (NSCLC), APE1 is highly expressed and associated with poor patient prognosis. The suppression of APE1 could lead to the accumulation of unrepaired DNA damage in cells. Therefore, APE1 is viewed as an important marker of malignant tumors and could serve as a potent target for the development of antitumor dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 56 publications
2
71
0
Order By: Relevance
“…A large number of studies have implicated dysfunctional DNA repair proteins, such as BRCA1, RAD51, FEN1, and Polβ, in BC initiation and progression ( Li et al, 2021 ; Lu et al, 2020 ; Martin et al, 2007 ; Thacker, 2005 ; Wang et al, 2019 ; Wang et al, 2020b ; Xia et al, 2021 ). Elevated DNA repair activity contributes to drug resistance and limits the efficacy of chemotherapeutic agents ( Long et al, 2021 ; Lu et al, 2020 ). Thus, targeting the DDR key proteins such as BRCA1 and BRCA2 is a potential effective therapeutic strategy for mono- or combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have implicated dysfunctional DNA repair proteins, such as BRCA1, RAD51, FEN1, and Polβ, in BC initiation and progression ( Li et al, 2021 ; Lu et al, 2020 ; Martin et al, 2007 ; Thacker, 2005 ; Wang et al, 2019 ; Wang et al, 2020b ; Xia et al, 2021 ). Elevated DNA repair activity contributes to drug resistance and limits the efficacy of chemotherapeutic agents ( Long et al, 2021 ; Lu et al, 2020 ). Thus, targeting the DDR key proteins such as BRCA1 and BRCA2 is a potential effective therapeutic strategy for mono- or combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies demonstrated inhibition of NSCLC progression in mice. These promising results following APE1 inhibition prompted further investigations into various small molecule inhibitors of the protein [131]. Gossypol is an inhibitor of APE1 involved in a phase III trial (ClinicalTrials.gov Identifier: NCT01977209) to assess its ability to improve the sensitivity of cisplatin-based chemotherapy in NSCLC patients with high APE1 expression (Table 1).…”
Section: Current Treatment Strategies and Future Perspectivesmentioning
confidence: 99%
“…The different expressions of immune checkpoints between high- and low-risk groups could be used to predict the clinical response of corresponding inhibitors and provide new insights into clinical treatment. The NCI-60 database, consisting of 60 different cancer cell lines from nine different types of tumors, was performed to investigate drug sensitivity through the CallMiner software ( ) ( 27 ). Finally, the Pearson correlation analysis was utilized to detect the association between the prognostic AG expression and 263 drugs approved by the Food and Drug Administration (FDA).…”
Section: Methodsmentioning
confidence: 99%